Pengaruh Metode Pembelajaran Diskusi Interaktif terhadap Peningkatan Pemahaman Siswa - Hariati, Neza; Suandi, Suandi; Mawarzani, Safka (Tirai Edukasi : Jurnal Pendidikan, 2025)
This study aims to analyze the effect of the interactive discussion learning method on improving students’ understanding in Class X at MAN 2 Central Lombok in Economics subjects. The background of this research is the low level of students’ understanding due to the dominance of lecture methods that tend to be passive. This research employed a quantitative approach with a quasi-experimental design (pretest-posttest control group design). The sample consisted of 34 students divided into two groups: the experimental class (interactive discussion) and the control class (conventional lecture). The research instrument was multiple-choice tests administered before and after treatment. Data analysis included normality test, homogeneity test, paired sample t-test, and independent sample t-test. The results revealed that the average posttest score of the experimental class (85.24) was higher than that of the control class (73.53). The t-test showed a significance value of 0.000 < 0.05, indicating that the interactive discussion method significantly improved students’ understanding. Thus, this method is proven effective and recommended as an alternative in Economics learning.